EFFECTS OF APPLICATION OF THE TWO-ROUND ELECTORAL SYSTEM FOR THE ELECTIONS OF THE MAYORS OF 2015 IN UKRAINE - Гнатенко, П. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The results of mayors’election of regional centers of 2015 in Ukraine are analyzed. Attention is focused on the indicators of the number of nominated candidates, candidates who passed the second round and elected mayors. It is pointed to the growing regionalization of Ukraine’s political system, which is associated with the growing role of local governments and their influence on regional processes. The obtained results for the three basic groups: parliamentary parties, extraparliamentary parties and self-nominees are compared.